Funding research in universities: do government resources act as a complement or substitute to industry funding?. Issue 1 (1st January 2020) - Wang, Yuandi; Chen, Yu; Li, Weiping; Wang, Tao; Guo, Lijia; Li-Ying, Jason; Huang, Jiashun
Abstract: The interactions between universities and businesses have become key drivers of today's economic growth and firms' business success. However, a key factor, the existing relationship between government and industry funding, is largely underexplored. This study investigates the relationship between government and industry funding for universities, in the context of developing countries, specifically taking China as a case. We found that there is a substitution effect between the two types of funding and this effect varies from different types of universities. We discuss our findings and draw implications for firms that seek to collaborate with universities.